Hippadine from Crinum jagus is active against ovarian carcinoma and melanoma cancer cell lines. - Ogah, Comfort Alicha; Ogah, Celina Onotse; Ajala, Olusegun Sampson; Igoli, John Igbaji; Gray, Alexander; Ferro, Valerie A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background Crinum jagus (Amaryllidaceae), has been used in folk medicine for the treatment of various diseases including cancer. The plant is rich in alkaloids and other phytoconstituents. This study aimed to isolate, and structurally elucidate compounds from Crinum jagus bulb (an Amaryllidaceae plant) and study the cytotoxic activity of hippadine on ovarian carcinoma (A2780) and melanoma cancer (A375) cell lines. Methods In this study, bulbs of C. jagus were extracted with methanol and fractionated with n-hexane, ethyl acetate, and methanol, Column chromatography was used to isolate and purify compounds while the identities of the compounds were confirmed using HRESI and 2D NMR spectroscopy. The cytotoxic activity of hippadine was evaluated on ovarian carcinoma (A2780) and melanoma cancer (A375) cell lines using a resazurin-based test (alamar blue assay). Results Hippadine, ?-sitosterol, stigmasterol, and 4’-hydroxy-7-methoxyflavan were isolated from the ethylacetate fraction of the bulbs. The identity of these compounds was further confirmed by comparing research data with other literature reports. This is an initial report of the flavan in Crinum jagus. The cytotoxic studies on hippadine gave IC50 values of 4.23± 0.35µg/ml on A2780 cells and 4.32 ± 0.55 µg/ml on A375 cells. Conclusions This study has justified the use of Crinum jagus bulb in folkloric medicine for the treatment of cancer. The phytochemical constituents hereby reported and the cytotoxic effect of hippadine provides a basis for further investigation into other pharmacological uses of Crinum jagus bulb as alkaloids are known for their diverse pharmacological activities.